Reassessing Missionary Spirituality: A Normative Scriptural Approach to the Formation of Korean Missionaries - Chun Young Lee; Professor Fazel Ebrihiam Freeks (Pharos Journal of Theology)
According to 2017 Korea World Missions Association statistical report, Korea is second largest missionary sending country among the nations. The number of missionaries dramatically increased in short period of time after the Expo’ 74 Mass Evangelism Movement at Yoido, Seoul, in1974. However, this radical growth causing crisis in their missions. The prominent problem is that they have lack of biblical and missiological principles of missional theology, anthropology, history and strategy. The lack of foundation mission cause to weaken their spirituality in their cross-cultural missions. Therefore, this paper aims to address the normative objectives inside the Osmer model (2008). The normative job provides insights into the fundamental reasons of the current situation, as well as contextual material that underscores the obstacles encountered by Korean missionaries about the biblical and missiological principles of missional theology, anthropology, history, and strategy. The normative task offers ethical and normative directives derived from Scripture.